Impact of maternal and perinatal characteristics on the evolution of the newborn - Lediana Dalla Costa; Poliana Cristina Freitas; Géssica Tuani Teixeira; Guilherme Costa; Vanessa Viana; Durcelina Schiavoni (Universidade Federal de Santa Maria, 2018)
Aim: to identify the impact of maternal and perinatal characteristics on the evolution of newborns admitted to the neonatal Intensive Care Unit. Method: A quantitative cross-sectional research carried out from April to June 2017 in a neonatal ICU of a reference hospital for high-risk gestation. Data collection was made possible through medical records and declarations of live births. The data were analyzed through the Statistical Package for the Social Sciences® (SPSS) software. Results: it has been demonstrated an association between death and extreme low birth weight (p<0,000), extreme prematurity (p<0,001) and Apgar index < 7 in the 1st minute of life (p<0,003). Regarding hospital discharge, there was the 5th minute Apgar > 7 strictly related (p<0,011). Conclusion: the perinatal characteristics were essential for the evolution of the newborn, however, the association between the newborn's evolution and the maternal characteristics was not clear.